A new player in the international bond market: Comparing the macroeconomic determinants of foreign-currency denominated debt before the inclusion of the renminbi in the SDR - Ferreira-Lopes, A.; Ribeiro, G.; Martins, L. F. (Emerging Markets Finance and Trade, 2025)
We assess how the main macroeconomic determinants of the Renminbi (CNY) internationalization compare with those of the four Special Drawing Rights (SDR) currencies, by using quarterly data for the shares of international bond issuances between 2009Q3 and 2015Q4, the period after the internationalization of the CNY and until the year before its inclusion in the SDR. We use the system-based model of Seemingly Unrelated Regressions (SUR). Results show that the CNY is the currency most affected by the determinants under study, presenting nonlinearities, indicating that its role in the International Monetary System (IMS) is evolving. Specifically, the CNY is influenced by the bilateral trade share, which exhibits evidence of an evolution from a small to a big currency. Determinants that are proxies for currency stability, such as the inflation rate and volatility against the SDR, show that the CNY has both a financing and an investment purpose, which is corroborated by the spread of government bond yields and FDI flows, which are determinants that influence currency choice in debt issuance. Stock market capitalization, representing financial market development, indicates a complementary relationship between financial assets. Furthermore, despite its growing importance in the IMS, the CNY retains a major role in Asia.